Wages, Innovation, and Employment in China - Belton M. Fleisher; William H. McGuire; Xiaojun Wang; Min Qiang Zhao (Institute of Labor Economics (IZA), 2017)
We investigate the role of factor-priced-induced innovation in mediating the employment impact of expanding production in China. Our empirical approach implements concepts developed in Acemoglu (2010) and complements the approaches summarized by Wei, Xie, and Zhang (2017) that focus on directly observable aspects of innovation (R&D, patent activity, etc.); labor-force characteristics including the availability of "surplus" labor, investments in human capital; and investments in physical capital. It complements work on the causes of a decline in labor's share in total output as documented in Bai and Qian (2010) and in Molero-Simarro (2017). Our empirical results to date support the hypothesis that wage-induced technology change has influenced productivity growth in China, at least in the decade of the 1990s, but perhaps less so or not at all after the middle of the next decade.
Keywords: O30; D22; D24; D33; 330; endogenous innovation; China; factor shares